A Preliminary Study on Mechanism of Phosphorus Solubilization by Phosphobacterium in Different Types of Soils - Abdul Jameel, A. (Asian Journal of Chemistry, 2010)
The phosphate solubilization by phospho bacteria was studied for four profile samples having different layers. The pH, electrical conductivity, total and available phosphorus were measured for each soil sample initially and after incubating for 3, 6, 9 and 12 days. An increase in the total and available phosphorus was observed as the incubation period was increased.